An Acceptance and Commitment Therapy (ACT)–Based Intervention for an Adult Experiencing Post-Stroke Anxiety and Medically Unexplained Symptoms. (April 2015) - Graham, Christopher D.; Gillanders, David; Stuart, Simon; Gouick, Joanna
To date, there is little support for the use of any psychotherapy to address post-stroke anxiety. Similarly, there have been no trials of acceptance and commitment therapy (ACT) for post-stroke anxiety, but clinician opinion suggests that an ACT approach may be effective in this context. In this case study, a high-functioning younger man with post-stroke anxiety and associated medically unexplained symptoms (chest pain and dizziness) was assessed and treated using an ACT approach. Mediators of change for both ACT (psychological flexibility) and cognitive therapy (illness perceptions) were recorded as were measures of depression, anxiety, and stress. By the end of treatment, the client was free of chest pain, had successfully returned to work, and had considerable reductions in anxiety, with smaller reductions in depression and stress. As outcomes improved, concomitant changes in psychological flexibility and illness perceptions were observed. The potential benefits offered by an ACT approach to post-stroke anxiety are discussed.